Engineering properties of fine-grained estuarine sediments in the Saint John River Valley at Fredericton, NB - Broster, Bruce E.; Daigle, Annie E.; Burtt, Gina M. (Atlantic Geoscience, 2014)
Fredericton, New Brunswick, is situated in an estuarine valley with its urban centre overlying up to 60 m of unconsolidated Late Wisconsinan-age glacigenic sediments. The discontinuous nature of units comprising the underlying sedimentary architecture represents challenges to engineering in the city. Major concerns have been the identification of pathways into the supply aquifer lying below the urban centre, and the sensitive nature of a buried fine-grained estuarine clay-silt unit. Results from a borehole drilled in the city centre were used to characterise the sediment units and recover samples from the estuarine unit for tests of engineering properties. These results and inclusion of published geophysical data represent the first detailed collection of engineering and sediment properties of the clay-silt unit at Fredericton.